An Analysis Classroom Techniques On Teaching Grammar At The Eleventh Grade Students Of SMK N 3 OKU - Arizah, Mila; Andesta, Tika Wilya (CV. Ridwan Publisher, 2019)
The objectives of the research were to knew the classroom techniques on teaching grammar at the eleventh grade students of SMK N 3 OKU that English teacher used. The population of this research were 5 English teachers. The researcher took 2 English teachers as the sample by applying total sampling. The data were collected through observation, interview and documentation. The researcher used descriptive qualitative approach to analyzing the data. The result of this research showed that all of the teachers used the classroom techniques of translation, drilling, brainstorming, and teacher-students exchange. The researcher concluded that English teachers at SMK N 3 OKU applied some classroom techniques on teaching grammar. Key Words: Classroom, Grammar, Technique